ASSA13-03-49 The Compare Study of the Protective Effects of Resveratrol and Atorvastatin to Oxidative Sresss on Human Umbilical Vein Endothelial Cells. (29th April 2013) - Yao, Lu; Ying, Li; Zhijun, Huang; Hong, Yuan
Abstract : Background and Objective: Oxidative stress plays an important role in atherosclerosis and endothelial cell is one of the initiating place of atherosclerosis. The oxidative-stress-induced endothelial dysfunction is the key pathway of atherosclerosis. NO, MDA, LDH, SOD are peroxidative products of lipid derived catalyzation. They are useful indexes of in vivo lipid peroxidation. Statins are anti—atherosclerosis drugs which widely are used in clinic practise. Previous studies indicated that the athero-protective effect may be related to the anti-oxidative effect. Resteratrol is a well-known anti-oxidative drug produced by a restricted number of plant species. The differences in anti-oxidative capabilities of statins and resveratrol may reflect their differences in anti-atherosclerosis activities. This study is aiming to assess the anti-oxidative effects of statins and resveratrol by inhibiting production of NO, MDA, LDH and SOD in peroxide hydrogen stimulated human umbilical vein endothelial cell (HUVEC). Methods: HUVEC were co-incubated in the same medium in presence of different concentrations of atorvastatin (1μmol/l) and resveratrol (1μmol/l, 5μmol/l, 10μmol/l) for 24 hours and also 48 hours, and in peroxide hydrogen (10 μmol/l) for 2 hours. After stimulation, the supernatants were collected to measure NO, MDA, LDH and SOD using enzyme-linked immunosorbent assays (ELISA). And the survival rates of HUVEC were detected by MTT assay. Results: Peroxide hydrogen at dose of l0μmol/l can induce enhanced oxidant stress in HUVECs. The values of MTT were significantly reduced, the content of NO (P < 0.01), MDA (P < 0.05), LDH (P < 0.05) increased and SOD (P μmol/l, and the content of SOD is lower. Resveratrol has dose-dependent inhibition effects of the production of MDA, NO and LDH, and it can significantly increase the content of SOD (5μmol/l vs 10μmol/l, P < 0.001). The content of MDA, NO and LDH of 48h resveratrol group is lower than the 24 hour resveratrol group (P < 0.05). There were also difference between the two groups of atovastatin. Conclusions: Resveratrol and atovastatin both have dose and time-dependent anti-oxidative effects. Resveratrol is more powerful in anti-oxidative stress activity than atovastatin. Resveratrol is a promising drug for the prevention and treatment of atherosclerosis in the future.